2019
DOI: 10.1210/clinem/dgz001
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Mitotane in Human Primary Adrenocortical Carcinoma Cultures

Abstract: Context Patients with adrenocortical carcinoma (ACC) often fail mitotane treatment and deal with severe toxicity, marking the relevance of predictive parameters for treatment outcome. Objective Determine the effects of mitotane in primary ACC cultures, and correlate sensitivity with patient and tumor characteristics. Methods In 32 primary ACC cultures, the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 34 publications
3
15
0
4
Order By: Relevance
“…For that reason, the achievement of the target range should be considered as the goal of the mitotane treatment [9]. Currently, no one of the proposed biomarkers, which were previously described to predict response and attainment of therapeutic plasma concentrations [14][15][16][17], is used in clinical practice since they have not been validated. In this multicenter study, we evaluated SNPs of CYP2W1 and CYP2B6 as potential predictive markers of response to mitotane in a large cohort of patients treated with mitotane monotherapy as first pharmacological therapy either after radical resection (group A) or in not completely resectable, recurrent or advanced ACC (group B).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For that reason, the achievement of the target range should be considered as the goal of the mitotane treatment [9]. Currently, no one of the proposed biomarkers, which were previously described to predict response and attainment of therapeutic plasma concentrations [14][15][16][17], is used in clinical practice since they have not been validated. In this multicenter study, we evaluated SNPs of CYP2W1 and CYP2B6 as potential predictive markers of response to mitotane in a large cohort of patients treated with mitotane monotherapy as first pharmacological therapy either after radical resection (group A) or in not completely resectable, recurrent or advanced ACC (group B).…”
Section: Discussionmentioning
confidence: 99%
“…We previously showed that ACC patients having high CYP2W1 immunostaining at tumor level present a better response to mitotane therapy in comparison to those with low CYP2W1 staining [15]. These results were very recently confirmed in primary ACC cell culture [16]. Currently, it is unclear whether SNPs of CYP2W1 might affect the metabolic function of the enzyme [23].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Boulate et al recently demonstrated a potentiating effect of rosuvastatin on mitotane cell toxicity in vitro [21]. Van Koetsveld et al showed that mitotane could have an increased in vitro sensitivity on cortisol-producing ACC tumors [13]. Cusato et al hypothesized that mitotane blood levels and dosage could be affected by body fat and seasonal variations in white and brown adipose tissue [22].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies showed that mitotane causes interference with cholesterol metabolism and with mitochondrial activity in adrenocortical cells, which often leads to an increase in the apoptosis rate. It also reduces adrenal steroidogenesis by inhibiting key mitochondrial enzymes like CYP11B, which reduces the conversion of hormone precursors into active hormones such as cortisol [11][12][13][14]. It was also found that mitotane could potentially interfere with pituitary function by comparing adrenocorticotropic hormone (ACTH) levels between patients treated with mitotane for ACC and patients with primary adrenal insufficiency (autoimmune or post-adrenalectomy) [15].…”
Section: Introductionmentioning
confidence: 99%